2021
DOI: 10.3201/eid2706.203964
|View full text |Cite
|
Sign up to set email alerts
|

Case–Control Study of Risk Factors for Acquired Hepatitis E Virus Infections in Blood Donors, United Kingdom, 2018–2019

Abstract: A substantial increase in locally acquired cases of hepatitis E virus (HEV) has been observed across Europe; a 10-fold increase of >21,000 cases of HEV was reported in the European Economic Area during 2005-2015 (1-4). It is diffi cult to accurately estimate the true burden of HEV due to substantial heterogeneity in available data across member states (5).An increasing trend of acute HEV cases was observed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In contrast, other studies from different contexts showed that the frequency of both male and female blood donors was nearly equal. For instance, the United States (51.7%), Belgium (54.6%), the United Kingdom (47.0%), the Netherlands (50.0%), Spain (54.0%), France (50.0%), Finland (45.0%), and Denmark (50.0%) [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies from different contexts showed that the frequency of both male and female blood donors was nearly equal. For instance, the United States (51.7%), Belgium (54.6%), the United Kingdom (47.0%), the Netherlands (50.0%), Spain (54.0%), France (50.0%), Finland (45.0%), and Denmark (50.0%) [ 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, the unique situation in Switzerland is most likely attributed to a high degree of self-sufficiency regarding Swiss pork consumption and the fact that Switzerland is not part of the European Economic Area [ 27 ]. In England and Wales, for example, the sequences found in humans are more closely related to porcine sequences from mainland Europe rather than the UK; most likely due to a high degree of imported pork [ 56 ]. Furthermore, due to the high animal health status of pigs in Switzerland, the import of live animals is strictly limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients whose immunity is unable to resist the virus have symptoms of acute viral hepatitis such as jaundice, hepatomegaly, vomiting, nausea, abdominal pain, and fever. In patients with low immunity, HEV causes chronic liver infection, liver failure, and extrahepatic symptoms 6,7 . Infection is the most common complication of viral liver disease and one of the main causes of death.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with low immunity, HEV causes chronic liver infection, liver failure, and extrahepatic symptoms. 6,7 Infection is the most common complication of viral liver disease and one of the main causes of death. Most of the pathogenic bacteria causing the infection of patients come from the normal gut microbiota, which is closely related to various biological mechanisms of the liver.…”
Section: Introductionmentioning
confidence: 99%